Conservation of Medicinal Plants in North Sumatra for Sustainable Use - Rahmawaty; Abdul Rauf; Arina, Hafizah; Afifuddin, Yunus (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Indonesia is one of the countries with the most significant biodiversity globally, and one of the essential biodiversity is medicinal plants. To maintain the sustainability of medicinal plants, it is necessary to conserve medicinal plants. This activity aims to collect and preserve medicinal plants found in North Sumatra Province. The implementation method consists of several stages of activities: making a collection and conservation hut for medicinal plants, preparation of planting media, planting, arrangement of seeds for collection of medicinal plants. Collection/collection of medicinal plant seeds from various sources, Giving names of medicinal plant species, Inauguration, and socialization of therapeutic plant collection and conservation lodges. The partner in this activity is the Pondok Miri Asri farmer group located in Sei Semayang Village, Sunggal District, Deli Serdang Regency, North Sumatra Province. More than 90 types of medicinal plants have been collected from Sei Semayang Village, from the Miri Asri cottage farmer group, and several districts in North Sumatra Province. With the existence of a place to collect medicinal plants, it is hoped that it will be helpful for the community and can be used sustainably.